Networking and cultural differences in Human Resource Management: The Case of Kazakhstan - Altynbekov, Mardan (2014)
The new emerging markets are becoming significant players in global market in recent decade. This study follows current pace in employing institutional theory to explore the specific pressures and factors makes networking essential in Human Resource Management in different countries. The study is a detailed qualitative analysis of networking and cultural differences in Kazakhstan, a country with very different value and government structure. Contrary to simplistic expectations, Kazakhstan shows a mix of the Soviet, the Western and the Oriental culture. The practices reflect many Kazakhstan institutional factors, but not in simple and direct ways. Institutional factors interact in intricate ways to create complex and dynamic pressures for the role of networking in Human Resource Management. The research should consider these interactions and dynamic processes with care and institutional theory can assist in providing an efficient intricate research framework.